Brain Penetration of the ROS1/ALK Inhibitor Lorlatinib Confirmed by PET. (20th October 2017) - Collier, T. Lee; Maresca, Kevin P.; Normandin, Marc D.; Richardson, Paul; McCarthy, Timothy J.; Liang, Steven H.; Waterhouse, Rikki N.; Vasdev, Neil
The Massachusetts General Hospital Radiochemistry Program, in collaboration with Pfizer, has developed unique 11 C and 18 F-labeling strategies to synthesize isotopologs of lorlatinib (PF-06463922) which is undergoing phase III clinical trial investigations for treatment of non-small-cell lung cancers with specific molecular alterations. A major goal in cancer therapeutics is to measure the concentrations of this drug in the brain metastases of patients with lung cancer, and penetration of the blood–brain barrier is important for optimal therapeutic outcomes. Our recent publication in Nature Communications employed radiolabeled lorlatinib and positron emission tomography (PET) studies in preclinical models including nonhuman primates (NHPs) that demonstrated high brain permeability of this compound. Our future work with radiolabeled lorlatinib will include advanced PET evaluations in rodent tumor models and normal NHPs with the goal of clinical translation.